Effect of dam silt addition to sandy soil on corn plant ( Zea mays. L) growth and its productive traits (Submission and Review of Research -Biological Sciences Series, 2025)
The research was carried out at the Sanobar Jableh Agricultural Scientific Research Station in Lattakia Governorate during the 2021/2022 agricultural season, with the aim of studying the effect of adding dam silt to sandy soil on the growth and development of yellow corn plants. The treatments were distributed between the silt addition levels (S5, S4, S3, 2) and the mineral fertilization treatment (S1)، in addition to the control treatment (SO)، according to a randomized complete block design (RCBD) with three replicates for each treatment. The studied plant indicators were (plant height - leaf surface area, vegetative weight, root weight, 100-grain weight). The silt addition quantities were calculated based on the clay content of both the soil and silt. The research results showed a significant increase in the studied traits for the addition levels compared to (S1) and (SO), where (S4) 25%, (S3 (20%), and (15%) raised the clay level in the surface layer of the studied soil to 30% (S5%), this led to a clear improvement in the studied plant characteristics compared to (S1) and (SO), as treatment (S5) gave the highest plant height (202.8 cm), which was positively reflected in the total leaf surface area (5465 cm2/plant), in addition to increasing the weight of the dry vegetative and root system of the plant and the weight of 100 grains/g directly with the levels of silt addition. Based on the above, it can be suggested to add Salah El-Din Dam silt to modify the texture of the sandy soil to act as a natural enhancer for the overall physical and chemical characteristics of the sandy soil, which in turn is positively reflected on the cultivated plant